Development of a patient-reported outcome measure of tophus burden: the Tophus Impact Questionnaire (TIQ-20). Issue 12 (11th August 2014) - Aati, Opetaia; Taylor, William J; Siegert, Richard J; Horne, Anne; House, Meaghan E; Tan, Paul; Drake, Jill; Stamp, Lisa K; Dalbeth, Nicola
Abstract : Background: Tophus burden is currently measured using physical examination and imaging methods. The aim of this study was to develop a patient-reported outcome (PRO) tool to assess tophus burden in people with gout. Methods: The responses from interviews with 25 people with tophaceous gout were used to generate items for a preliminary PRO tool. Following cognitive testing of each item, a preliminary 34-item questionnaire was administered to 103 people with tophaceous gout. Rasch analysis generated a 20-item Tophus Impact Questionnaire (TIQ-20). Test-retest reproducibility and construct validity of the TIQ-20 were assessed. Results: The TIQ-20 responses fit the Rasch model and demonstrated unidimensionality, adequate precision, absence of differential item functioning and adequate person separation index. The TIQ-20 included items related to pain, activity limitation, footwear modification, participation, psychological impact and healthcare use due to tophi. In the 103 patients with tophaceous gout, floor effects were observed in 4.9% and ceiling effects in 1%. The TIQ-20 test-retest intraclass correlation coefficient was 0.76 (95% CI 0.61 to 0.85). All predicted correlations for construct validity testing were observed, including weak correlation with serum urate concentrations (r<0.30), moderate correlation with subcutaneous tophus count and dual energy CT urate volume (r=0.30–0.50), and stronger correlation with Health Assessment Questionnaire scores (r>0.50). Conclusions: We have developed a tophus-specific PRO in patients with tophaceous gout. The TIQ-20 demonstrates acceptable psychometric properties. Initial results show internal, face and construct validity, reproducibility and feasibility. Further research is required to determine responsiveness to change.